2013
DOI: 10.1590/s1808-16572013000100011
|View full text |Cite
|
Sign up to set email alerts
|

Ação de inseticidas sobre os ovos e lagartas da broca-pequena-do-fruto do tomate, em bioensaio de laboratório

Abstract: 73Ação de inseticidas sobre os ovos e lagartas da broca-pequena-do-fruto do tomate, em bioensaio de laboratório.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In the larval stage, this species feeds on the fruit pulp causing severe damages that make the tomato unsuitable for marketing. In certain regions, losses of up to 90% were recorded due to outbreaks of N. elegantalis (Miranda et al ., 2005; Bortoli et al ., 2013). Recognizing the economic importance and the potential of this species spreading to other regions, the European and Mediterranean Plant Protection Organization (EPPO) recently listed N. elegantalis as a quarantine pest in Europe (EPPO, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the larval stage, this species feeds on the fruit pulp causing severe damages that make the tomato unsuitable for marketing. In certain regions, losses of up to 90% were recorded due to outbreaks of N. elegantalis (Miranda et al ., 2005; Bortoli et al ., 2013). Recognizing the economic importance and the potential of this species spreading to other regions, the European and Mediterranean Plant Protection Organization (EPPO) recently listed N. elegantalis as a quarantine pest in Europe (EPPO, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In leaf bioassays, no differences in mortality for teflubenzuron alone or in mixture with adjuvants on SBL strains were detected. Contrary to this, adjuvants added to the insecticide spray of other biosynthesis chitin inhibitors (flufenoxuron, triflumuron, novaluron, and lufenuron) increased the mortality of N. elegantalis (DE BORTOLI et al, 2013). In laboratory and field applications of chlorantraniliprole and flubendiamide, the addition of adjuvants increased the mortality of A. transitella (DEMKOVICH et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies indicated that adjuvants added to diamides increased the mortality of adults of Amyelois transitella (Walker, 1863) (Lepidoptera: Pyralidae) (DEMKOVICH et al, 2018). This was also verified when adjuvants were added to indoxacarb and cartap to control Neoleucinodes elegantalis (Guenée, 1854) (Lepidoptera: Pyralidae) (DE BORTOLI et al, 2013), to thiamethoxam + lambda-cyhalothrin against Enneothrips flavens Moulton, 1941 (Thysanoptera: Thripidae) (CALORE et al 2015), and dimethoate and spinetoram to control Thrips tabaci Lind., 1888 (Thysanoptera: Thripidae) (NEGASH et al, 2020).…”
Section: Introductionmentioning
confidence: 83%